2023
DOI: 10.1021/acs.jpcb.3c01619
|View full text |Cite
|
Sign up to set email alerts
|

The Analytical Flory Random Coil Is a Simple-to-Use Reference Model for Unfolded and Disordered Proteins

Abstract: Denatured, unfolded, and intrinsically disordered proteins (collectively referred to here as unfolded proteins) can be described using analytical polymer models. These models capture various polymeric properties and can be fit to simulation results or experimental data. However, the model parameters commonly require users’ decisions, making them useful for data interpretation but less clearly applicable as stand-alone reference models. Here we use all-atom simulations of polypeptides in conjunction with polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 92 publications
1
16
0
Order By: Relevance
“…While our analysis is necessarily retrospective and correlative, it is in line with prior experimental work. , To explore this observation further, we performed all-atom simulations using the ABSINTH implicit solvent model of the p53 with three phosphomimetic mutations (S15E, T18E, and S20E) and compared the result to previous simulations of the wildtype sequence (Figure A) . While glutamic acid is an imperfect analogue for the phosphate group, the results revealed that relatively modest changes in linear charge density can cause local and long-range changes in the...…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…While our analysis is necessarily retrospective and correlative, it is in line with prior experimental work. , To explore this observation further, we performed all-atom simulations using the ABSINTH implicit solvent model of the p53 with three phosphomimetic mutations (S15E, T18E, and S20E) and compared the result to previous simulations of the wildtype sequence (Figure A) . While glutamic acid is an imperfect analogue for the phosphate group, the results revealed that relatively modest changes in linear charge density can cause local and long-range changes in the...…”
Section: Resultssupporting
confidence: 74%
“…Comparison of changes in local and global dimensions for wildtype vs phosphomimetic versions of p53. (A) Scaling maps where inter-residue distances for the phosphomimetic version of the p53 N-terminal domain (p53 ) are normalized by distances for the wildtype protein. Despite differing by only three residues in the N-terminal quarter of the protein, the phosphomimetic version of p53 shows substantial differences in long-range and local dimensions, as shown by the emergence of both attractive (blue) and repulsive (red) interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous efforts have contributed to building a general theoretical framework for understanding the impact of crowding on disordered proteins, linking the protein response to fundamental properties of the sequence, such as the scaling exponent. While the scaling exponent reflects the monomer–solvent and monomer–monomer interactions, and therefore depends on the primary structure of the protein, different disordered proteins may attain the same scaling exponent through completely different sequence compositions. Sequence-specific effects are relatively unexplored, but they can encode for nonspecific affinities for crowding agents, modulate conformations across different length scales, and even introduce transient secondary structure motifs. Furthermore, the contribution of macromolecular crowding has been previously tested only for full-length IDPs.…”
mentioning
confidence: 99%